Review : Kajian Potensi Bakteri Endofit sebagai Agen Biodegradasi Linear Alkylbenzene Sulfonate (LAS) - Mahmudah, Arini Nurul; Faizah, Hanik; Munir, Misbakhul (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Linear Alkylbenzene Sulfonate (LAS) is a type of anionic surfactant which is commonly used as a raw material in making commercial detergents or cleaners. Even though LAS can be degraded naturally in the environment, detergent wastewater containing LAS still needs to be treated properly before being discharged into the environment. One way that can be done to reduce the toxic effects of LAS is biodegradation. The use of bacteria, especially endophytic bacteria associated with plants, is known to have potential as a biodegradation agent for LAS. This review aims to examine the potential of endophytic bacteria as LAS biodegradation agents. The method used in this review is a literature review from several international and national journal references. Data were analyzed descriptively and presented in narrative and table form. The results of the research show that several species of endophytic bacteria isolated from various types of plants have the potential to degrade pollutants, such as heavy metals, benzene, phenol, phenanthrene (PHE), diesel, ammonium, phosphate, COD, and hydrocarbons which also shows that endophytic bacteria have the potential to degrades LAS.